THE PROCESS OF CHARACTERIZATION OF RELIGIOUS MODERATION IN MULTICULTURAL SCHOOLS BASED ON LIVING VALUES EDUCATION - Al Faruq, Umar (Proceeding of International Conference on Islamic Education (ICIED); Vol 7 No 1 (2022): Proceeding of International Conference on Islamic Education (ICIED), 2022)
This study seeks to reveal in-depth the religious moderation character education process at the multicultural school Selamat Pagi Indonesia Senior High School of Batu. This empirical study uses a qualitative approach with a type of case studies. The data were obtained through field observations, in-depth interview processes, and document studies. The results showed that the process of religious moderation character education process at the multicultural school Selamat Pagi Indonesia Senior High School of Batu was carried out from the beginning of the arrival of students at school and was continuous until they completed the learning process at the multicultural school Selamat Pagi Indonesia Senior High School of Batu. The religious moderation character education process is carried out through the doctrine of religious moderation values that align with the values contained in Living Values Education. Moreover, the character education process of religious moderation is also carried out by providing direct experience and habituation to all students in various activities that reflect religious moderation both in the school and the dormitory environment. Furthermore, the religious moderation character education process at Selamat Pagi Indonesia Senior High School is also carried out in the form of good exemplary from teachers and supervisors in schools and dormitories.